'SASA! is the medicine that treats violence'. Qualitative findings on how a community mobilisation intervention to prevent violence against women created change in Kampala, Uganda - Nambusi Kyegombe; Elizabeth Starmann; Karen M. Devries; Lori Michau; Janet Nakuti; Tina Musuya; Charlotte Watts; Lori Heise (Taylor & Francis Group, 2014)
Background: Intimate partner violence (IPV) violates women's human rights and is a serious public health concern. Historically strategies to prevent IPV have focussed on individuals and their relationships without addressing the context under which IPV occurs. Primary prevention of IPV is a relatively new focus of international efforts and what SASA!, a phased community mobilisation intervention, seeks to achieve. Methods: Conducted in Kampala, Uganda, between 2007 and 2012, the SASA! Study is a cluster randomised controlled trial to assess the community-level impact of SASA! This nested qualitative study explores pathways of individual- and community-level change as a result of SASA! Forty in-depth interviews with community members (20 women, 20 men) were conducted at follow-up, audio recorded, transcribed verbatim and analysed using thematic analysis complemented by constant comparative methods. Results: SASA! influenced the dynamics of relationships and broader community norms. At the relationship level, SASA! is helping partners to explore the benefits of mutually supportive gender roles; improve communication on a variety of issues; increase levels of joint decision-making and highlight non-violent ways to deal with anger or disagreement. Not all relationships experienced the same breadth and depth of change. At the community level, SASA! has helped foster a climate of non-tolerance of violence by reducing the acceptability of violence against women and increasing individuals' skills, willingness, and sense of responsibility to act to prevent it. It has also developed and strengthened community-based structures to catalyse and support on-going activism to prevent IPV. Discussion: This paper provides evidence of the ways in which community-based violence prevention interventions may reduce IPV in low-income settings. It offers important implications for community mobilisation approaches and for prevention of IPV against women. This research has demonstrated the potential of social norm change interventions at the community level to achieve meaningful impact within project timeframes.